2021
DOI: 10.2147/ijgm.s314393
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index for Predicting the Prognosis of Critically Ill Patients with Acute Pancreatitis

Abstract: Background Systemic immune-inflammation index (SII) has been identified as a prognostic biomarker in various diseases. However, its significance in acute pancreatitis (AP) has not been reported. Therefore, the main aim of this study was to determine the association of SII with clinical outcomes of AP patients, after adjusting for several confounders. Methods This retrospective cohort study was conducted using data retrieved from the Medical Information Mart for Intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In a retrospective study with 513 patients with pancreatitis, the high SII group (>755 × 10 9 /L) had a significantly higher rate of 30-day all-cause mortality (HR = 2.57; 95% CI = 1.35–4.88). [ 114 ] The study did not examine the utility of SII in predicting severe acute pancreatitis or in-hospital mortality.…”
Section: Systemic Immune-inflammation Indexmentioning
confidence: 99%
“…In a retrospective study with 513 patients with pancreatitis, the high SII group (>755 × 10 9 /L) had a significantly higher rate of 30-day all-cause mortality (HR = 2.57; 95% CI = 1.35–4.88). [ 114 ] The study did not examine the utility of SII in predicting severe acute pancreatitis or in-hospital mortality.…”
Section: Systemic Immune-inflammation Indexmentioning
confidence: 99%
“…Although the severity of AP can be clinically assessed through multifactor scoring systems and imaging studies, the emergence of biomarkers and predictive models provide another effective method for the diagnosis of patients with AP [46]. Previous study indicated that the systemic immune inflammatory index could comprehensively reflect the disease characteristics of AP [47]. Thus, we screened for biomarkers that could predict AP severity based on immune-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…The SII was initially developed to reflect the balance of host inflammatory and immune status, which could predict the outcome in patients with hepatocellular carcinoma [ 5 ]. Recently, it has been investigated as a prognostic factor for various cancers [ 6 , 7 ], inflammatory status [ 8 , 9 ], and coronary disease [ 10 ]. The systemic inflammation response index (SIRI), which is also calculated from peripheral blood cells, has similar characteristics to those of the SII [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been investigated as a prognostic factor for various cancers [ 6 , 7 ], inflammatory status [ 8 , 9 ], and coronary disease [ 10 ]. The systemic inflammation response index (SIRI), which is also calculated from peripheral blood cells, has similar characteristics to those of the SII [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%